A comparison of pull control policies in hybrid production systems - Çadırcı, Özge. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Environmental concerns trigger companies for utilizing reuse activities as much as possible, gradually. One of these activities is remanufacturing process. When manufacturing process is combined with remanufacturing process, the system is referred to as a hybrid production system. This study concentrates on a hybrid production system that performs both remanufacturing and manufacturing activities under pull type production control. The incoming demand is satisfied by the output of either process, where remanufactured products are assumed to be restored into “as good as new” condition. In the study, four of the most common pull control systems, viz. Kanban Control System (KCS), Base Stock Control System (BSCS), Generalized Kanban Control System (GKCS) and Extended Kanban Control System (EKCS), are compared on the single-stage hybrid production system considered. A stochastic model is developed for each of the four control policies. Then these models are analyzed using methods based on the previous studies available in the literature in order to obtain performance measures of interest. After comparing the outcomes of analytical models with the simulation results to test accuracy, a cost function is defined using the performance measures. Then this cost function is minimized with respect to the control parameters of each control mechanism. Finally, results derived from numerical experimentation are obtained, and conclusions are drawn.
Keywords: Remanufacturing.; Production control.; Just-in-time systems.; Inventory control.